Slope stability of streambanks at saturated riparian buffer sites. Issue 6 (16th September 2021) - Dickey, Loulou C.; McEachran, Andrea R.; Rutherford, Cassandra J.; Rehmann, Chris R.; Perez, Michael A.; Groh, Tyler A.; Isenhart, Thomas M.
Abstract: Saturated riparian buffers (SRBs) reduce nitrate export from agricultural tile drainage by infusing drainage water into carbon‐rich riparian soils where denitrification and plant uptake occur. The water quality benefits from SRBs are well documented, but uncertainties about their effect on streambank stability have led to design standards that limit the maximum bank height and minimum buffer width, thus reducing the number of suitable candidate sites. In this study, the relationship between SRB design and streambank stability was examined through numerical slope stability modeling and validated using field sites. At the study sites, the addition of SRB flow increased the probability of failure by less than 3% for both simulated dry and rainfall scenarios. Furthermore, the simulations provide no evidence to support excluding potential sites based on bank height alone. Multivariate analysis of dimensionless parameters developed for SRB flow conditions was used to predict the factor of safety as a function of the SRB site and design conditions. The equation presented allows designers to assess the stability of a potential site where bank failure poses a heightened risk. The results of this study alleviate the need for extensive geotechnical evaluations at future SRB sites and could increase SRB implementation by expanding the range of eligible sites. Core Ideas: The addition of saturated riparian buffers flow did not cause streambank instability in 97% of simulated cases. Stability prior to saturated riparian buffers installation is a good indicator of postinstallation stability. Bank height is not a significant determinant of streambank stability. SRB flow increased the probability of streambank failure by less than 3%.